Disorders/Differences of Sex Development (DSD) and Gender Dysphoria: The Need of a National Guideline for Malaysia - Ani Amelia Zainuddin; Rafidah Hanim Mokhtar; Atikah Muhammad Noor Choliq; Taqwa Zabidi; Nuur Asyikin Mohd Shukor; Salasiah Hanin Hamjah; Muhammad Yazid Jalaludin (IIUM Press, 2025)
Indexed by Scopus (Tier 2)